Credit risk management and financial performance of Islamic Bank listed on Bursa Malaysia / Fatin Nadia Shamsudin - Shamsudin, Fatin Nadia (Faculty of Business and Management, 2018)
The purpose of this study is to identify the relationship between credit risk management and Malaysian Islamic banks' profitability. Data were collected from year 2007 until 2017 for 15 Islamic bank listed on Bursa Malaysia. The financial ratios used are bank performance and credit risk. Profitability is measured by Return on Assets (ROA) while the credit risk indicated by Total Loan to Total Assets (TLTA), Total Loan to Total Deposit (TLTD), Capital Adequacy Ratio (CAR), Loan Loss Provision (LLP) and NonPerforming Loan (NPL). In order to get the results, the data were tested by using descriptive statistics, correlation analysis and also regression analysis.